2013
DOI: 10.1364/ol.38.001449
|View full text |Cite
|
Sign up to set email alerts
|

Reflection measurements to reveal the absorption in nanowire arrays

Abstract: The absorption of light is at the core of photovoltaic applications. For many nanostructure-based devices, an assessment of the absorption in the nanostructures is complicated by a thick, opaque substrate that prohibits transmission measurements. Here, we show how a single reflection measurement can be used for approximating the amount of light absorbed in vertical semiconductor nanowire arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…This is consistent with previous work on untapered NWs that demonstrated that the absorption peak red-shifts with increasing diameter. 17,24 This behavior is also seen in Fig. 4(c), which shows absorption spectra of untapered NWs over a range of diameters.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…This is consistent with previous work on untapered NWs that demonstrated that the absorption peak red-shifts with increasing diameter. 17,24 This behavior is also seen in Fig. 4(c), which shows absorption spectra of untapered NWs over a range of diameters.…”
supporting
confidence: 65%
“…Image sensors whose pixels show wavelength selective absorption would enable multispectral imaging without these hardware additions. Nanowires that have been extensively studied for broadband light absorption applications such as for solar cells [16][17][18] also show tunable light absorption. Such wavelength selective absorption has been demonstrated with horizontal nanowires (NWs) 19,20 and vertical NW arrays.…”
mentioning
confidence: 99%
“…In this way, nanowires have proven to efficiently concentrate light and enhance absorption. Moreover, this absorption can be tuned by modifying the nanowire geometry making them act as nanoantennas for light. Despite extensive theoretical and experimental investigations on light absorption in nanowire arrays and in solar cells, , the angle-dependent light absorption in individual nanowires remains largely unexplored. , Typically, only the two limiting cases for the illumination are reported in the literature: (i) nanowires lying on the substrate illuminated perpendicular to their axis that are described as Mie scatterers, , and (ii) vertical nanowires illuminated parallel to their axis that support guided modes to which the incident light can couple and be absorbed. ,, Recently, the experimental comparison of the external quantum efficiency of vertical and horizontal single-nanowire solar cells has shown that nanowires exhibit a larger photocurrent when illuminated parallel to their axis . However, this comparison was performed on different devices that did not contain the same nanowire and the intrinsic differences in the samples might have an impact on the results.…”
Section: Nanowire Descriptionmentioning
confidence: 99%
“…16−20 Despite extensive theoretical and experimental investigations on light absorption in nanowire arrays and in solar cells, 17,21−28 the angle-dependent light absorption in individual nanowires remains largely unexplored. 29,30 Typically, only the two limiting cases for the illumination are reported in the literature: (i) nanowires lying on the substrate illuminated perpendicular to their axis that are described as Mie scatterers, 28,31−33 and (ii) vertical nanowires illuminated parallel to their axis that support guided modes to which the incident light can couple and be absorbed. 18,19,34 Recently, the experimental comparison of the external quantum efficiency of vertical and horizontal single-nanowire solar cells has shown that nanowires exhibit a larger photocurrent when illuminated parallel to their axis.…”
mentioning
confidence: 99%
“…The absorbing properties of the single diameter InP NW arrays can be modified by adjusting their geometrical parameters by Nicklas Anttu et al [53]. Both theoretical study and experimental measurements were adopted to verify their conclusions [54]. The geometrical dimensions of the InP NWs were optimized as 180 nm.…”
Section: Nanowiresmentioning
confidence: 99%